Domestication of Indigenous Timber Species in Degraded Open Karst Lands: A Decade of Experience - Bullecer, Rumila Cilocilo (JPAIR Multidisciplinary Research, 2008)
This study assessed the domestication potential of 43 indigenous timber species on 1.2 hectares of degraded karst land. The survival, height growth, diameter growth, and site factors were monitored periodically. The results showed that 28 indigenous forest timber species thrived in the open karst area, including eight dipterocarps: narig, mayapis, white lauan, bagtikan, guisok-guisok, manggasinoro, red lauan, and yakal-kaliot. Non-dipterocarps included hitanggol and kalilangan. Species with 100% survival rates were aniam gubat, bayokbok, ipil, kalumpit, jamog, puso-puso, sagimsim, and taluto. White lauan achieved a survival rate of 96%, while molave reached 92%. Kalumpil exhibited the highest growth increments in both height and diameter, followed by dao, duguan, and milipili. Among the dipterocarps, white lauan showed the highest diameter and height growth increments. Narig demonstrated tolerance to full solar exposure due to its waxy leaf surface. The study suggests that domestication farms should integrate fruit trees, vegetable trees (such as Gnetum gnemon), and other economic plants. Future trials should include domesticating barit, anisag, sudiang, other dipterocarps, bago, nito, sig-id, rattan, and other raw materials for handicrafts.
Keywords: Indigenous Timber Species; Domestication of Timber Species; Karst Land Rehabilitation; Dipterocarps; Indigenous Forest Species